Perceived stress, resilience, and stress coping in patients with drug resistant epilepsy and functional dissociative seizures. (October 2022) - Gargiulo, Ángel JM; Sarudiansky, Mercedes; Videla, Alejandro; Lombardi, Nicolás; Korman, Guido P; Oddo, Silvia; D´Alessio, Luciana
Highlights: Depression and anxiety are psychiatric disorders related to chronic stress. Levels of perceived stress, resilience, and the styles of stress coping were studied. Patients with functional dissociative seizures (FDS) showed higher levels of depression and anxiety. Patients with DRE (drug resistant epilepsy) and FDS showed higher levels of stress variables compared to controls. Similar levels of perceived stress, resilience and stress coping were found in FDS and DRE. Abstract: Purpose: Depression and anxiety are psychiatric disorders related to chronic stress, commonly found in patients with drug-resistant epilepsy (DRE) and functional dissociative seizures (FDS). The present study compares the levels of perceived stress, resilience, and the styles of stress coping among patients with DRE (n=60), FDS (n=28), and controls (n=31). Methods: We performed a cross-sectional study. All patients underwent Video Electroencephalography to confirm the diagnosis and completed the psychiatric assessment (SCID I and II of DSM IV) supported by several instruments validated in Spanish. Results: FDS scored higher in perceived stress (p = 0.004) with lower levels of resilience compared to controls (p = 0.01). Stress coping subscales show higher scores in negative self-focus and hostility in patients with FDS compared to controls (p=0.003). Similarly, DRE patients scored higher in perceived stress (p = 0.001), and presented lower levels of resilience (p = 0.004) with higher levels of hostility compared to controls (p=0.02). However, no significant differences were found between FDS and DRE on stress coping variables. Anxiety scores and depression rates were higher in the FDS group compared to DRE (p=0.008) and higher in DRE compared to controls (p<0.05). A positive correlation between depression and perceived stress was found (r = 0.6, p=0.0001). Conclusions: Our results delineate a more detailed picture of the psychological profile of this population, emphasizing the importance of stress factors in patients with FDS and DRE. Combined intervention strategies which enhance stress coping may be appropriate to direct treatment and psychotherapy.